The negative impact of α‐ketoglutarate dehydrogenase complex deficiency on matrix substrate‐level phosphorylation. Issue 6 (8th March 2013) - Kiss, Gergely; Konrad, Csaba; Doczi, Judit; Starkov, Anatoly A.; Kawamata, Hibiki; Manfredi, Giovanni; Zhang, Steven F.; Gibson, Gary E.; Beal, M. Flint; Adam‐Vizi, Vera; Chinopoulos, Christos
Abstract : A decline in α‐ketoglutarate dehydrogenase complex (KGDHC) activity has been associated with neurodegeneration. Provision of succinyl‐CoA by KGDHC is essential for generation of matrix ATP (or GTP) by substrate‐level phosphorylation catalyzed by succinyl‐CoA ligase. Here, we demonstrate ATP consumption in respiration‐impaired isolated and in situ neuronal somal mitochondria from transgenic mice with a deficiency of either dihydrolipoyl succinyltransferase (DLST) or dihydrolipoyl dehydrogenase (DLD) that exhibit a 20–48% decrease in KGDHC activity. Import of ATP into the mitochondrial matrix of transgenic mice was attributed to a shift in the reversal potential of the adenine nucleotide translocase toward more negative values due to diminished matrix substrate‐level phosphorylation, which causes the translocase to reverse prematurely. Immunoreactivity of all three subunits of succinyl‐CoA ligase and maximal enzymatic activity were unaffected in transgenic mice as compared to wild‐type littermates. Therefore, decreased matrix substrate‐level phosphorylation was due to diminished provision of succinyl‐CoA. These results were corroborated further by the finding that mitochondria from wild‐type mice respiring on substrates supporting substrate‐level phosphorylation exhibited 30% higher ADP‐ATP exchange rates compared to those obtained from DLST +/– or DLD +/– littermates. We propose that KGDHC‐associated pathologies are a consequence of the inability of respiration‐impaired mitochondria to rely on "in‐house" mitochondrial ATP reserves.—Kiss, G., Konrad, C., Doczi, J., Starkov, A. A., Kawamata, H., Manfredi, G., Zhang, S. F., Gibson, G. E., Beal, M. F., Adam‐Vizi, V., Chinopoulos, C. The negative impact of α‐ketoglutarate dehydrogenase complex deficiency on matrix substrate‐level phosphorylation. FASEB J. 27, 2392–2406 (2013). www.fasebj.org